Diagnosis and recommendation integrated system 1. Formulation of DRIS norms for Hevea brasiliensis - Joseph M; Mathew M; Ranganathan C R; Sethuraj M R (Indian Journal of Natural Rubber Research, 1993)
The diagnosis and recommendation Integrated System (DRIS) involves the use of nutrient concentration ratios to determine the relative sufficiency of nutrients within the plant tissue. A data bank comprising yield, leaf nutrient concentration for nitrogen (N), phosphorus (P), potassium (K), calcium (Ca) and magnesium (Mg) and soil fertility status from 1200 individual fields from 15 estates representing the major rubber growing regions of South India was built. DRIS norms for the nutrients N, P, K, Ca and Mg were developed from a regrouped data set having uniformity in age and system of tapping. The variance ratio (low yield/high yield) was highly significant for the nutrient combinations involving Mg indicating the direct role of Mg on latex yield. The mean valuesa and the corresponding cv from the high yielding population for the ratio N/P, K/N, K/P, Ca/N, Ca/P, Ca/K, Ca/Mg, N/Mg, P/Mg and K/Mg were selected as the standard norms.
Keywords: Data bank; DRIS; Foliar diagnosis; Hevea brasiliensis; India